Estimating the time period between infection and diagnosis based on CD4+ counts at first diagnosis among HIV-1 antiretroviral naïve patients in Nigeria - Joseph C Forbi; Thanda D Forbi; Simon M Agwale (Journal of Infection in Developing Countries)
Introduction: CD4+ T-cell levels are an important criterion for categorizing HIV-related clinical conditions. Late diagnosis of infection contributes to poor medical outcomes and the continuation of viral transmission. This population-based cohort study in north central Nigeria reports the initial CD4+ lymphocyte counts at the time of first HIV diagnosis and determines the approximate time interval when HIV infection was acquired..